An Investigation into Bay Allocation Model and Algorithm for Outbound Containers - Chen Xie; Wei Yan (2008 International Symposium on Knowledge Acquisition and Modeling : 21-22 December 2008, 2008)
A bay allocation model is developed for outbound containers at container terminal based on objective programming, which aims at the problem of stack bay allocation for outbound containers. The modelpsilas objective function is subject to the minimization of the moving distance of the yard crane when bringing outbound containers into yard and loading ships. To resolve the model, a hybrid algorithm which employs heuristic rule and distributed genetic algorithm, is then employed. Finally, a case simulation study has been used for system illustration, and then verifies the validity and usefulness of the model and the algorithm.